Method for recovering lithium in aluminum-based adsorbent
Through the mixing and ball milling of strong acid solution and aluminum-based adsorbent, combined with ultrasonic treatment and dilute acid leaching technology, the problem of low lithium recovery in aluminum-based adsorbents is solved, efficient lithium recycling and resource recycling is achieved, and production is reduced Cost and process complexity.
Patent Information
- Application Number
- CN202411282135.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-17
AI Technical Summary
In the prior art, lithium recovery rate in aluminum-based adsorbents is low and energy consumption is high, and the process flow is complex, resulting in high production costs and reduced adsorbent activity.
A strong acid solution is mixed with aluminum-based adsorbent and ball milled, combined with ultrasonic treatment, and a lithium-containing solution is obtained by solid-liquid separation and concentrated. Then, a carbon source is added to the lithium-rich solution to form lithium carbonate products, using dilute acid leaching and mechanical activation technology Improve the leaching rate and recovery rate of lithium.
It significantly improves the recovery rate of lithium in aluminum-based adsorbents, reduces production costs, improves product purity and process simplicity and feasibility, and ensures efficient lithium recycling and resource recycling.
Smart Images

Figure CN119143157A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium resource utilization, and in particular to a method for recovering lithium from an aluminum-based adsorbent. Background Art
[0002] Lithium is widely used in lithium-ion batteries, aviation materials, lithium-based grease, aluminum electrolysis, glass and ceramic industries, air conditioning, medicine, and organic synthesis industries. Adsorption is one of the commonly used methods for extracting lithium from salt lakes. It requires a short cycle, has low requirements for conditions, can achieve raw halogen lithium extraction and industrial continuous production. Aluminum hydroxide is an aluminum-based lithium adsorbent skeleton with high selectivity, good stability, simple operation, and high recovery rate. The main process of lithium extraction by adsorption is to mix aluminum salt and lithium chloride, lithium sulfate or lithium nitrate solution evenly, then add sodium hydroxide solution to stir the reaction, and further synthesize the adsorbent LiX·2Al(OH)3·nH2O (X is Cl - 、SO4 2- 、NO3 - ), and then lithium is removed by further desorption, but the production cost of this operation is high, and the anions will block the pores, causing the adsorbent activity to decrease.
[0003] Extracting lithium from the alumina production process is one of the current research hotspots. According to research, lithium mainly exists in the form of Li2CO3·nAl(OH)3·nH2O in the production of aluminum hydroxide. In the prior art, lithium is extracted from sodium aluminate solution by adsorption to produce lithium-rich adsorbents, and then lithium is analyzed by high-temperature and high-pressure hydrothermal leaching. However, there are problems such as low lithium recovery rate, high energy consumption, and complex process flow. Therefore, how to improve the recovery rate of lithium in aluminum-based adsorbents is a technical problem that needs to be solved urgently. Summary of the invention
[0004] The present application provides a method for recovering lithium from an aluminum-based adsorbent to solve the following technical problem: how to improve the recovery rate of lithium from an aluminum-based adsorbent.
[0005] The present application provides a method for recovering lithium from an aluminum-based adsorbent, wherein the aluminum-based adsorbent contains lithium, and the method comprises:
[0006] The aluminum-based adsorbent is mixed with a strong acid solution and ball-milled to obtain a mixed slurry;
[0007] The mixed slurry is subjected to ultrasonic treatment at a set temperature and holding time to leach lithium from the aluminum-based adsorbent, and then the mixed slurry after the ultrasonic treatment is subjected to solid-liquid separation to obtain a lithium-containing solution and a lithium-depleted aluminum-based adsorbent;
[0008] Concentrating the lithium-containing solution to obtain a lithium-rich solution; and
[0009] A carbon source is added to the lithium-rich solution to obtain a lithium carbonate product.
[0010] Optionally, the lithium content of the aluminum-based adsorbent is 0.60%-0.80% by mass.
[0011] Optionally, the concentration of the strong acid solution is 0.6 g / L-1.0 g / L.
[0012] Optionally, the ball milling time is 10 min-15 min.
[0013] Optionally, the solid content of the mixed slurry is 250 g / L-300 g / L, and the particle size D50 of the mixed slurry is 10 μm-15 μm.
[0014] Optionally, the set temperature of the ultrasonic treatment is 25°C-60°C, and the set insulation time of the ultrasonic treatment is 1.0h-3.0h.
[0015] Optionally, the lithium concentration of the lithium-containing solution is 1.4 g / L-1.6 g / L.
[0016] Optionally, the lithium concentration of the lithium-rich solution is 15.0 g / L-20.0 g / L.
[0017] Optionally, the carbon source includes one or more of CO2 and carbonates.
[0018] Optionally, the purity of the lithium carbonate product is ≥98%, and the recovery rate of lithium in the aluminum-based adsorbent is ≥90%.
[0019] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0020] The present application provides a method for recovering lithium from an aluminum-based adsorbent, wherein the aluminum-based adsorbent contains lithium, comprising: mixing and ball-milling the aluminum-based adsorbent with a strong acid solution to obtain a mixed slurry; subjecting the mixed slurry to ultrasonic treatment at a set temperature and insulation time to leach the lithium in the aluminum-based adsorbent, and then subjecting the mixed slurry after ultrasonic treatment to solid-liquid separation to obtain a lithium-containing solution and a lithium-depleted aluminum-based adsorbent; concentrating the lithium-containing solution to obtain a lithium-rich solution; and adding a carbon source to the lithium-rich solution to obtain a lithium carbonate product. The aluminum-based adsorbent is acid-leached with a strong acid solution. During the acid-leaching process, the dilute acid solution contacts the aluminum-based adsorbent, and Li2CO3·nAl(OH)3·nH2O is converted into LiX and separated from aluminum hydroxide through a chemical reaction. At the same time, the combined application of mechanical activation and ultrasonic technology produces a significant synergistic effect, which not only accelerates the speed of the acid-leaching reaction, but also increases the lithium leaching rate. Thereby, the recovery rate of lithium in the aluminum-based adsorbent is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0022] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0023] Figure 1 A flow chart of a method for recovering lithium from an aluminum-based adsorbent provided in an embodiment of the present application;
[0024] Figure 2 A schematic diagram of a method for recovering lithium from an aluminum-based adsorbent provided in an embodiment of the present application. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0026] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0027] In addition, in the description of the specification of the present application, the terms "including", "comprising", etc. mean "including but not limited to". In this article, relational terms such as "first" and "second", etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A and B can be singular or plural. In this article, "at least one" means one or more, and "plurality" means two or more. "At least one", "the following at least one item (items)" or similar expressions refer to any combination of these items, including any combination of single items (items) or plural items (items). For example, "at least one of a, b, or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e. a and b), ac, bc or abc, where a, b, c can be single or plural, respectively.
[0028] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0029] The creative ideas of this application are:
[0030] The Li2CO3·nAl(OH)3·nH2O in the aluminum-based adsorbent is leached with a strong acid solution. During the leaching process, the amount of acid is properly controlled. The dilute acid solution contacts the aluminum-based adsorbent and the lithium in the Li2CO3·nAl(OH)3·nH2O is converted into ions (Li +) is released into the solution and combines with acid ions to form LiX. Aluminum is mainly retained in the solid phase in the form of aluminum hydroxide (Al(OH)3). At the same time, the combination of mechanical activation and ultrasonic technology is adopted. Mechanical activation pre-treats the aluminum-based adsorbent by physical means to refine its particles, increase its specific surface area, and improve its reaction activity. Ultrasonic treatment can effectively destroy the structure of the aluminum-based adsorbent, increase the solid-liquid contact area, promote the leaching of lithium, and further improve the reaction activity, thereby greatly improving the leaching rate of lithium. The combined application of these two technologies has produced a significant synergistic effect, which not only accelerates the speed of the acid leaching reaction, but also increases the leaching rate of lithium. Compared with a single technology, the combined technology can more effectively release lithium from the aluminum-based adsorbent while maintaining the stability of aluminum in the solid phase. After the mechanical activation and ultrasonic treatment are completed, the lithium-containing solution is separated from the de-lithium aluminum-based adsorbent by solid-liquid separation technology (such as filtration, centrifugation, etc.). After the lithium is removed, the aluminum-based adsorbent (mainly aluminum hydroxide) can be returned to the alumina production process and continue to be used as an adsorbent, which not only extends the service life of the adsorbent, but also realizes the recycling of resources and reduces the overall production cost. The lithium-containing solution can be further concentrated, precipitated or ion exchanged to prepare lithium carbonate products.
[0031] In summary, the present application adopts a combination of dilute acid leaching and optimization techniques, and the amount of aluminum dissolved in the lithium recovery process is effectively reduced, thereby reducing the aluminum impurity content in the lithium carbonate product. This not only improves the purity of the product, but also reduces the difficulty and cost of subsequent processing.
[0032] Figure 1 A flow chart of a method for recovering lithium from an aluminum-based adsorbent provided in an embodiment of the present application; Figure 2 A schematic diagram of a method for recovering lithium from an aluminum-based adsorbent provided in an embodiment of the present application.
[0033] See also Figure 1 and Figure 2 The present application provides a method for recovering lithium from an aluminum-based adsorbent, wherein the aluminum-based adsorbent contains lithium, and the method comprises:
[0034] S1, mixing and ball-milling the aluminum-based adsorbent and a strong acid solution to obtain a mixed slurry;
[0035] The aluminum-based adsorbent is mixed with an appropriate amount of a strong acid solution (such as hydrochloric acid, sulfuric acid, nitric acid, etc.) and ball-milled. This step is intended to increase the contact area between the reactants and promote the release of lithium from the aluminum-based adsorbent. The ball-milled mixture forms a uniform mixed slurry.
[0036] In some embodiments, the aluminum-based adsorbent has a lithium content of 0.60% to 0.80% by mass.
[0037] In some embodiments, the concentration of the strong acid solution is 0.6 g / L-1.0 g / L.
[0038] In the process of lithium recovery in aluminum-based adsorbents, dilute acid leaching is an effective and environmentally friendly method. By controlling the acid concentration in the range of 0.6-1.0g / L, it is possible to ensure that lithium ions are effectively removed from the aluminum hydroxide skeleton while avoiding the dissolution of a large amount of aluminum, thereby reducing the impurity content in the lithium carbonate product. The dilute acid concentration limits the amount of aluminum dissolved because the dissolution rate of aluminum is slower at lower acidity. This helps to keep the main form of aluminum in the lithium-free aluminum-based adsorbent as aluminum hydroxide, which is convenient for subsequent recovery and reuse. Although the acid concentration is low, it can be effectively promoted to remove lithium from the adsorbent with the assistance of physical means such as ultrasonic treatment and ball milling. Exemplary, the concentration of the strong acid solution can be 0.6g / L, 0.7g / L, 0.8g / L, 0.9g / L, 1.0g / L, etc.
[0039] In some embodiments, the ball milling time is 10 min-15 min.
[0040] In some embodiments, the solid content of the mixed slurry is 250 g / L-300 g / L, and the particle size D50 of the mixed slurry is 10 μm-15 μm.
[0041] The ball milling time is limited to 10-15min, the solid content of the mixed slurry is 250-300g / L, and the particle size D50 is 10-15μm to ensure that the particle size of the aluminum-based adsorbent in the mixed slurry is moderate. If the ball milling time exceeds 15min, the aluminum-based adsorbent particle size is too fine, and returning to the alumina production process will cause filtration difficulties. If the ball milling time is less than 10min, the aluminum-based adsorbent particle size is coarse, resulting in a decrease in the subsequent lithium leaching rate. Exemplarily, the ball milling time is 10min, 11min, 12min, 13min, 14min, 15min, etc., the solid content of the mixed slurry can be 250g / L, 260g / L, 270g / L, 280g / L, 290g / L, 300g / L, etc., and the particle size D50 of the mixed slurry can be 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, etc.
[0042] S2, subjecting the mixed slurry to ultrasonic treatment at a set temperature and holding time to leach lithium from the aluminum-based adsorbent, and then subjecting the mixed slurry after the ultrasonic treatment to solid-liquid separation to obtain a lithium-containing solution and a lithium-removed aluminum-based adsorbent;
[0043] The mixed slurry is placed under a set temperature for ultrasonic treatment and kept warm for a period of time. Ultrasonic treatment can effectively destroy the structure of the aluminum-based adsorbent and promote the leaching of lithium. After the treatment is completed, the lithium-containing solution is separated from the de-lithium aluminum-based adsorbent by solid-liquid separation technology (such as filtration, centrifugation, etc.).
[0044] In some embodiments, the set temperature of the ultrasonic treatment is 25° C.-60° C., and the set insulation time of the ultrasonic treatment is 1.0 h-3.0 h.
[0045] Ultrasonic treatment can effectively destroy the internal structure of aluminum-based adsorbents through the cavitation effect, microjet and shock wave phenomena generated by high-frequency sound waves in liquids, so that lithium ions that were originally tightly bound to the adsorbent can be released into the solution. Compared with traditional chemical methods, this physical method has higher efficiency and milder conditions, which can reduce the use of chemical reagents and environmental pollution. The temperature of ultrasonic treatment is limited to 25℃-60℃, and the insulation time is 1.0h-3.0h. Lower temperatures may not be enough to promote the full leaching of lithium, while too high temperatures may cause the solution to evaporate too quickly, increase energy consumption and even damage the equipment. The length of the insulation time directly affects the leaching efficiency of lithium. A shorter insulation time may not allow all lithium ions to be effectively released, while too long a time may increase energy consumption and cost, and may also lead to an increase in other impurities in the solution. Illustratively, the temperature of ultrasonic treatment can be 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, etc., and the insulation time can be 1.0 h, 1.5 h, 2.0 h, 2.5 h, 3.0 h, etc.
[0046] In some embodiments, the lithium concentration of the lithium-containing solution is 1.4 g / L-1.6 g / L.
[0047] S3, concentrating the lithium-containing solution to obtain a lithium-rich solution; and
[0048] The separated lithium-containing solution is concentrated to remove most of the water to obtain a lithium-rich solution. This step can be achieved by evaporation, reverse osmosis, ion exchange and other methods.
[0049] In some embodiments, the lithium concentration of the lithium-rich solution is 15.0 g / L-20.0 g / L.
[0050] The lithium concentration of the lithium-rich solution is limited to 15.0g / L-20.0g / L. Within this concentration range, the concentration of lithium ions is moderate, which is conducive to the stable progress of subsequent chemical reactions and avoids a decrease in reaction rate or an increase in side reactions caused by too high or too low concentrations. At the same time, too high a concentration may increase the energy consumption of subsequent processing steps and aggravate the corrosion of equipment. The appropriate concentration can reduce these unfavorable factors while ensuring the treatment effect. In addition, from the perspective of economic benefits, a moderate lithium concentration can reduce production costs and energy consumption while ensuring recovery rate and purity. Exemplarily, the lithium concentration of the lithium-rich solution can be 15.0g / L, 16.0g / L, 17.0g / L, 18.0g / L, 19.0g / L, 20.0g / L, etc.
[0051] In some embodiments, the concentration is carried out by one or more combinations of evaporation, membrane concentration, rotary evaporation or ultrafiltration.
[0052] S4. Adding a carbon source to the lithium-rich solution to obtain a lithium carbonate product.
[0053] An appropriate amount of carbon source (such as sodium carbonate, ammonium carbonate, etc.) is added to the lithium-rich solution to generate lithium carbonate precipitate through chemical reaction. Subsequently, the lithium carbonate product can be obtained through filtering, washing, drying and other steps.
[0054] In some embodiments, the carbon source includes one or more of CO2 and carbonates.
[0055] In some embodiments, the purity of the lithium carbonate product is ≥98%, and the recovery rate of lithium in the aluminum-based adsorbent is ≥90%.
[0056] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.
[0057] Example 1
[0058] This embodiment provides a method for recovering lithium from an aluminum-based adsorbent, which may include the following steps:
[0059] S11, mixing a lithium-containing 0.80% aluminum-based adsorbent and 0.6 g / L hydrochloric acid, and ball milling for 10 min to obtain a 300 g / L mixed slurry;
[0060] S21, placing the mixed slurry in an ultrasonic water bath at 60° C. for 3.0 h, filtering and solid-liquid separation to obtain a 1.6 g / L lithium-containing solution, and washing the filter cake and returning it to the alumina production process;
[0061] S31, concentrating the lithium-containing solution by a rotary evaporator to obtain a lithium-rich solution with a lithium concentration of 20.00 g / L;
[0062] S41. CO2 is introduced into the lithium-rich solution to precipitate lithium carbonate, which is then washed and dried to obtain industrial-grade lithium carbonate with a purity of ≥98%.
[0063] Example 2
[0064] This embodiment provides a method for recovering lithium from an aluminum-based adsorbent, which may include the following steps:
[0065] S11, mixing a lithium-containing 0.60% aluminum-based adsorbent and 1.0 g / L hydrochloric acid, and ball milling for 15 min to obtain a 250 g / L mixed slurry;
[0066] S21, placing the mixed slurry in an ultrasonic water bath at 25° C. for 1.0 h, filtering and solid-liquid separation to obtain a 1.4 g / L lithium-containing solution, and washing the filter cake and returning it to the alumina production process;
[0067] S31, concentrating the lithium-containing solution by a rotary evaporator to obtain a lithium-rich solution with a lithium concentration of 15.00 g / L;
[0068] S41. Na2CO3 is added to the lithium-rich solution to precipitate lithium carbonate, which is then washed and dried to obtain industrial-grade lithium carbonate with a purity of ≥98%.
[0069] Example 3
[0070] This embodiment provides a method for recovering lithium from an aluminum-based adsorbent, which may include the following steps:
[0071] S11, mixing a lithium-containing 0.75% aluminum-based adsorbent and 0.8 g / L hydrochloric acid, and ball milling for 12 min to obtain a 280 g / L mixed slurry;
[0072] S21, placing the mixed slurry in an ultrasonic water bath at 45°C for 2.0 hours, filtering to separate the solid and liquid to obtain a 1.5 g / L lithium-containing solution, and returning the filter cake to the alumina production process after washing;
[0073] S31, concentrating the lithium-containing solution by a rotary evaporator to obtain a lithium-rich solution with a lithium concentration of 18.00 g / L;
[0074] S41. CO2 is introduced into the lithium-rich solution to precipitate lithium carbonate, which is then washed and dried to obtain industrial-grade lithium carbonate with a purity of ≥98%.
[0075] Example 4
[0076] This embodiment provides a method for recovering lithium from an aluminum-based adsorbent, which may include the following steps:
[0077] S11, mixing a lithium-containing 0.60% aluminum-based adsorbent and 0.6 g / L hydrochloric acid, and ball milling for 15 min to obtain a 250 g / L mixed slurry;
[0078] S21, placing the mixed slurry in an ultrasonic water bath at 45°C for 3.0 hours, filtering and solid-liquid separation to obtain a 1.5 g / L lithium-containing solution, and returning the filter cake to the alumina production process after washing;
[0079] S31, concentrating the lithium-containing solution by a rotary evaporator to obtain a lithium-rich solution with a lithium concentration of 16.00 g / L;
[0080] S41. Add solid K2CO3 to the lithium-rich solution to precipitate lithium carbonate, which is then washed and dried to obtain industrial-grade lithium carbonate with a purity of ≥98%.
[0081] Example 5
[0082] This embodiment provides a method for recovering lithium from an aluminum-based adsorbent, which may include the following steps:
[0083] S11, mixing a lithium-containing 0.70% aluminum-based adsorbent and 0.8 g / L hydrochloric acid, and ball milling for 10 min to obtain a 270 g / L mixed slurry;
[0084] S21, placing the mixed slurry in an ultrasonic water bath at 55° C. for 2.0 h, filtering the solid-liquid separation to obtain a 1.5 g / L lithium-containing solution, and returning the filter cake to the alumina production process after washing;
[0085] S31, concentrating the lithium-containing solution by a rotary evaporator to obtain a lithium-rich solution with a lithium concentration of 17.00 g / L;
[0086] S41. CO2 is introduced into the lithium-rich solution to precipitate lithium carbonate, which is then washed and dried to obtain industrial-grade lithium carbonate with a purity of ≥98%.
[0087] Comparative Example 1
[0088] The main difference between this comparative example and Example 5 is that in step S21, no ultrasound is performed, and only heat preservation treatment is performed.
[0089] The specific contents of this comparative example are as follows:
[0090] This comparative example provides a method for recovering lithium from an aluminum-based adsorbent, which may include the following steps:
[0091] S11, mixing a lithium-containing 0.70% aluminum-based adsorbent and 0.8 g / L hydrochloric acid, and ball milling for 10 min to obtain a 270 g / L mixed slurry;
[0092] S21, placing the mixed slurry in a 55°C water bath for 2.0 hours, filtering to separate the solid and liquid to obtain a 1.1 g / L lithium-containing solution, and washing the filter cake before returning it to the alumina production process;
[0093] S31, concentrating the lithium-containing solution by a rotary evaporator to obtain a lithium-rich solution with a lithium concentration of 17.00 g / L;
[0094] S41. CO2 is introduced into the lithium-rich solution to precipitate lithium carbonate, which is then washed and dried to obtain industrial-grade lithium carbonate with a purity of ≥98%.
[0095] Comparative Example 2
[0096] The main difference between this comparative example and Example 5 is that ball milling is not performed in step S11.
[0097] The specific contents of this comparative example are as follows:
[0098] This comparative example provides a method for recovering lithium from an aluminum-based adsorbent, which may include the following steps:
[0099] S11, mixing a lithium-containing 0.70% aluminum-based adsorbent and 0.8 g / L hydrochloric acid to obtain a 270 g / L mixed slurry;
[0100] S21, placing the mixed slurry in an ultrasonic water bath at 55° C. for 2.0 h, filtering and solid-liquid separation to obtain a 1.2 g / L lithium-containing solution, and washing the filter cake and returning it to the alumina production process;
[0101] S31, concentrating the lithium-containing solution by a rotary evaporator to obtain a lithium-rich solution with a lithium concentration of 17.00 g / L;
[0102] S41. CO2 is introduced into the lithium-rich solution to precipitate lithium carbonate, which is then washed and dried to obtain industrial-grade lithium carbonate with a purity of ≥98%.
[0103] Comparative Example 3
[0104] The main difference between this comparative example and Example 5 is that: no ball milling is performed in step S11, and no ultrasound is performed in step S21, and only heat preservation treatment is performed.
[0105] The specific contents of this comparative example are as follows:
[0106] This comparative example provides a method for recovering lithium from an aluminum-based adsorbent, which may include the following steps:
[0107] S11, mixing a lithium-containing 0.70% aluminum-based adsorbent and 0.8 g / L hydrochloric acid to obtain a 270 g / L mixed slurry;
[0108] S21, placing the mixed slurry in a water bath at 55° C. for 2.0 h, filtering to separate the solid and liquid to obtain a 0.9 g / L lithium-containing solution, and washing the filter cake before returning it to the alumina production process;
[0109] S31, concentrating the lithium-containing solution by a rotary evaporator to obtain a lithium-rich solution with a lithium concentration of 17.00 g / L;
[0110] S41. CO2 is introduced into the lithium-rich solution to precipitate lithium carbonate, which is then washed and dried to obtain industrial-grade lithium carbonate with a purity of ≥98%.
[0111] Table 1 Lithium concentration and lithium recovery rate of lithium-containing solution
[0112]
[0113] As can be seen from Table 1, through the lithium recovery method in an aluminum-based adsorbent provided in the embodiments of the present application, compared with Example 5, Comparative Example 1 did not use an ultrasonic water bath, and as a result, the concentration of lithium in the lithium-containing solution and the lithium recovery rate were reduced; compared with Example 5, Comparative Example 2 did not perform ball milling, and as a result, the concentration of lithium in the lithium-containing solution and the lithium recovery rate were reduced; Comparative Example 3 is different from Example 5 in that no ultrasound and ball milling are used, and as a result, the concentration of lithium in the lithium-containing solution and the lithium recovery rate are significantly reduced.
[0114] In addition, one or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:
[0115] In the embodiment of the present invention, Li2CO3·nAl(OH)3·nH2O in the aluminum-based adsorbent is converted into LiX and separated from aluminum hydroxide by acid leaching, and the combined application of ultrasonic and mechanical activation technologies greatly improves the leaching rate of lithium.
[0116] In the embodiment of the present invention, the lithium recovery rate is greater than 90%, the purity of the lithium carbonate product is greater than or equal to 98%, the moisture content of the lithium carbonate product is less than 0.20%, and the lithium carbonate product has high purity and stable quality, reaching the standard of industrial-grade lithium carbonate products.
[0117] In the embodiments of the present invention, a method for recovering lithium from an aluminum-based adsorbent is provided, which has a simple process, is easy to operate, has strong industrial feasibility, and can significantly reduce production costs.
[0118] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A method for recovering lithium from an aluminum-based adsorbent, characterized in that: The aluminum-based adsorbent contains lithium, and the method comprises: The aluminum-based adsorbent is mixed with a strong acid solution and ball-milled to obtain a mixed slurry; The mixed slurry is subjected to ultrasonic treatment at a set temperature and holding time to leach lithium from the aluminum-based adsorbent, and then the mixed slurry after the ultrasonic treatment is subjected to solid-liquid separation to obtain a lithium-containing solution and a lithium-depleted aluminum-based adsorbent; Concentrating the lithium-containing solution to obtain a lithium-rich solution; and A carbon source is added to the lithium-rich solution to obtain a lithium carbonate product.
2. The method according to claim 1, characterized in that Calculated by mass fraction, the lithium content of the aluminum-based adsorbent is 0.60%-0.80%.
3. The method according to claim 1, characterized in that The concentration of the strong acid solution is 0.6 g / L-1.0 g / L.
4. The method according to claim 1, characterized in that: The ball milling time is 10 min-15 min.
5. The method according to claim 1, characterized in that The solid content of the mixed slurry is 250 g / L-300 g / L, and the particle size D50 of the mixed slurry is 10 μm-15 μm.
6. The method according to claim 1, characterized in that The set temperature of the ultrasonic treatment is 25° C.-60° C., and the set insulation time of the ultrasonic treatment is 1.0 h-3.0 h.
7. The method according to claim 1, characterized in that The lithium concentration of the lithium-containing solution is 1.4 g / L-1.6 g / L.
8. The method according to claim 1, characterized in that The lithium concentration of the lithium-rich solution is 15.0 g / L-20.0 g / L.
9. The method according to claim 1, characterized in that: The carbon source includes one or more of CO2 and carbonate.
10. The method according to claim 1, characterized in that The purity of the lithium carbonate product is ≥98%, and the recovery rate of lithium in the aluminum-based adsorbent is ≥90%.
